2020
DOI: 10.1002/sdtp.14024
|View full text |Cite
|
Sign up to set email alerts
|

62‐4: Ultrathin Cu‐Ag Anode for High Light Outcoupling Efficiency by Eliminating Waveguide Mode in OLED

Abstract: Extracting light from the waveguide mode in organic lightemitting diodes (OLED) is most challenging as such optical mode is intrinsically formed due to materials and layered structure used in the device. Here, we show that a metal-only transparent conductor based an ultrathin Cu-Ag film can be used to eliminate the guided mode, thus enhancing light extraction efficiency in OLED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In addition, the devices exhibit significant bending capability and stability compared to ITO-based devices. In their subsequent studies, it was found that Cu-doped Ag would be more suitable compared to Al, because Cu has higher binding energy to the substrate or oxide [ 110 ].…”
Section: Ultrathin Metal Transparent Electrodementioning
confidence: 99%
“…In addition, the devices exhibit significant bending capability and stability compared to ITO-based devices. In their subsequent studies, it was found that Cu-doped Ag would be more suitable compared to Al, because Cu has higher binding energy to the substrate or oxide [ 110 ].…”
Section: Ultrathin Metal Transparent Electrodementioning
confidence: 99%
“…Our previous works showed that the ultrathin Ag alloy is highly flexible and can even enhance outcoupling efficiency of OLEDs by suppressing waveguide mode formation (4,5). Ag alloy with two adjacent dielectric layers, called dielectric-metal-dielectric (DMD) electrode, is more widely used in many applications since DMD forms ultrasmooth surface and is compatible with the conventional OLED structure and fabrication processes (6)(7)(8).…”
Section: Objective and Backgroundmentioning
confidence: 99%